Implementasi Terapi Spiritual Emotional Freedom Technique (SEFT) untuk Menurunkan Ansietas Akibat Hipertensi di Wilayah Kerja UPT Puskesmas Biru Kabupaten Bone - Alfian Mas’ud; Megawati Sibulo; Hikmah Damaiyanti (Jurnal Anestesi, 2025)
Based on the above data suggests that hypertension becomes a condition that is often undiagnosed or not well controlled. Hypertensive patients often find anxiety due to high blood pressure. So if it's not handled properly, there's a risk of complications. One of the treatments given is non-pharmacological therapy such as the Spiritual Emotional Freedom Technique (SEFT) therapy to reduce anxiety. This research aims to implement the Spiritual Emotional Freedom Technique (SEFT) therapy to reduce anxiety caused by hypertension. This study uses case study methods with data collection techniques through observations, interviews, physical examinations, documentation, and observation sheets, and the Hamilton Anxiety Rating Scale (HARS) questionnaire. After performing Spiritual Emotional Freedom Technique (SEFT) therapy for 15 minutes in the course of 3 days obtained anxiety result decreased, from anxieties moderate to no anxiety. From the results of the evaluation it can be concluded that the administration of Spiritual Emotional Freedom Technique (SEFT) therapy effectively reduces the anxiety caused by hypertension.